Adipose-Derived Mesenchymal Stem Cells Combined With Extracellular Vesicles May Improve Amyotrophic Lateral Sclerosis - Wang, Xichen; Zhang, Yong; Jin, Tian; Botchway, Benson O. A.; Fan, Ruihua; Wang, Lvxia; Liu, Xuehong (Frontiers in Aging Neuroscience, 2022)
The complexity of central nervous system diseases together with their intricate pathogenesis complicate the establishment of effective treatment strategies. Presently, the superiority of adipose-derived mesenchymal stem cells (ADSCs) on neuronal injuries has attracted significant attention. Similarly, extracellular vesicles (EVs) are potential interventional agents that could identify and treat nerve injuries. Herein, we reviewed the potential effects of ADSCs and EVs on amyotrophic lateral sclerosis (ALS) injured nerves, and expound on their practical application in the clinic setting. This paper predominantly focused on the therapeutic role of ADSCs concerning the pathogenesis of ALS, the protective and reparative effects of EVs on nerve injury, as well as the impact following the combined usage of ADSCs and EVs in ALS.